2015
DOI: 10.1007/s00784-015-1653-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of A. actinomycetemcomitans strains in subgingival samples from periodontitis subjects in Morocco

Abstract: A. actinomycetemcomitans can be frequently found in Morocco. This fact can influence the therapeutic approach of this type of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Several studies have investigated the possible association between the different serotypes of A. actinomycetemcomitans and periodontal condition in humans. Of the seven A. actinomycetemcomitans serotypes, a ‐ c are the most prevalent in whites, Asians, Africans, and Latin Americans; and serotype b is isolated most often from diseased periodontal sites in patients affected with periodontitis and seldom detected in subjects without periodontitis . In fact, the highly leukotoxic JP2 clone strains of A. actinomycetemcomitans , which belong to the serotype b , have been strongly associated with initiation and progression of aggressive forms of periodontitis and frequently detected in periodontitis patients living in geographically widespread areas, particularly individuals of African descent …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the possible association between the different serotypes of A. actinomycetemcomitans and periodontal condition in humans. Of the seven A. actinomycetemcomitans serotypes, a ‐ c are the most prevalent in whites, Asians, Africans, and Latin Americans; and serotype b is isolated most often from diseased periodontal sites in patients affected with periodontitis and seldom detected in subjects without periodontitis . In fact, the highly leukotoxic JP2 clone strains of A. actinomycetemcomitans , which belong to the serotype b , have been strongly associated with initiation and progression of aggressive forms of periodontitis and frequently detected in periodontitis patients living in geographically widespread areas, particularly individuals of African descent …”
Section: Discussionmentioning
confidence: 99%
“…Studies from 1998 forward examined a broad spectrum of bacteria using DNA technologies (Table ) . In one‐half the studies Aggregatibacter actinomycetemcomitans was implicated as a risk marker, and in another half Porphyromonas gingivalis , Tannerella forsythia , and Selenomonads emerged as markers of risk (Table ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies from 1998 forward examined a broad spectrum of bacteria using DNA technologies ( Table 2). [23][24][25][26][27][28][29][30][31][32][33][34][35][36] In one-half the studies Aggregatibacter actinomycetemcomitans was implicated as a risk marker, and in another half Porphyromonas gingivalis, 23,25,27,[32][33][34][35] Tannerella forsythia, 27,29,32,34,35 and Selenomonads emerged as markers of risk (Table 2). A recent study 37 showed that in younger individuals A. actinomycetemcomitans was associated with disease whereas this was not the case in older subjects.…”
Section: Relevant Findingsmentioning
confidence: 99%
“…An updated list of studies that aimed at elucidating various aspects concerning characteristics, function, occurrence, geographic dissemination, and the role of the JP2 clone in periodontitis is presented by Haubek and Johansson in 2014 [47]. Recently, JP2 clone strains have been isolated in Thai population [48], in Brazilians and their family members [49], in Spain [50], from periodontitis subjects in Morocco [51] and from marginal periodontitis in the mixed dentition [52]. The relationship between the colonization with the JP2 clone of Aa and the development of periodontal attachment loss in adolescents, longitudinal studies have been published [53–56].…”
Section: The Isolation and Studies Of Super‐leukotoxic Strain Aa Jp2mentioning
confidence: 99%